Intelligent Electronic Arbitration: A Blockchain-Based Model - Labanieh, Mohamad Fateh; Hussain, Mohammad Azam; Rahman, Rohana Abdul; Ayub, Zainal Amin (Multidisciplinary Applied Research and Innovation, 2022)
Blockchain has been regarded as a cornerstone and linchpin of Fourth Industrial Revolution (IR.4.0). Numerous sectors, including healthcare, have examined the use of blockchain technology. In this article, intelligent electronic arbitration (IEA) is an innovative and revolutionary dispute resolution mechanism that integrates artificial intelligence (AI) technologies within electronic arbitration (e-arbitration). The shift towards using the IEA mechanism in resolving commercial disputes is being sparked by the need to ensure sustainability in the practice of arbitration in Malaysia and the pressing necessity to facilitate access to justice during the COVID-19 outbreak or any unstable circumstances. However, using the IEA mechanism is not totally immune to criticisms. Firstly, when a losing party fails to comply with the IEA award, the winning party must undertake the traditional enforcement procedures. This result in further judicial proceedings, unnecessary expenses, and undue time-consuming. Secondly, the parties to IEA are vulnerable to the risk that their sensitive data and information shared during the IEA proceedings are not secure against cyber-attacks. This article introduces the applicability of the blockchain-based model in enhancing and strengthening the implementation of IEA. Therefore, the qualitative research methodology is adopted. Both primary and secondary data are collected using a library-based approach and analysed using critical and analytical approaches. It has been discovered that using IEA in a Blockchain-Based Model promises to clinch the above issues. Particularly, blockchain would eliminate the need to go through a long process to enforce the IEA award since such award would be self-enforced and without the intervention of the Malaysian High Courts. Additionally, the secured nature of blockchain would dramatically minimise the risk of cyber-attacks deriving from conducting the IEA procedures on the cyber-space. Finally, future research might quantitatively analyse the impact of using the blockchain-based model in enhancing and strengthening the implementation of the IEA mechanism.